EVALUATION OF ENVIRONMENTAL IMPACTS IN COPPER MINING COMPANIES USING INTERACTION NETWORKS - Martim, Hélio Cardoso; Santos, Vivianni Marques Leite dos (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Mining is one of the major sectors of the Brazilian economy, providing essential resources for its development. The obtained copper leaching is responsible for obtaining cathodes with a purity of 99.9% copper, which has a wide range of industrial applications. However, any mining operations cause the rise of diverse environmental impacts. These impacts should be assessed so that there is constant search for actions that promote their mitigation. The environmental impact assessment is a fundamental tool for the development of environmental management process of any enterprise. In this regard the use of interaction networks for environmental impact assessment is a methodology that allows the identification of these impacts in different orders and the interaction between them. The use of this tool in this study allowed the identification of the activities that generate the greatest number of environmental impacts, such as the extraction of malachita. This analysis can be used as a diagnostic tool for the implementation of measures to prevent or correct negative impacts to the environment, promoting the sustainability.